Effects of Coconut Water-Based Extender on Motility, Viability, Morphology and Membrane Integrity of Refrigerated (4°C) Canine Spermatozoa - Meena, Abhay Kumar; Saraswat, Chandra Shekher; Yadav , Sumit Prakash (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The objective of this study was to determine the effect of a coconut water-based extender on the quality parameters of dog semen (n=24  ejaculates) during refrigeration (4°C) preservation up to 72 h. Four ejaculates per dog were collected from 6 dogs by digital manipulation.  All fresh ejaculates were evaluated for macroscopic and microscopic semen evaluation tests. The semen samples were then extended  in a coconut water-based extender using a split sample technique. The diluted semen was kept in a refrigerator for preservation at 4°C  and evaluated at 0, 24, 48, and 72 h for sperm quality parameters. The sperm motility significantly reduced over a period of time from  0 to 72 h. The live sperm percentage did not differ significantly at 0, 24 and 48 h of preservation. However, there was a significant drop  in live sperm percentage at 72 h. The percent sperm abnormalities were significantly increased from 24, 48 to 72 h of preservation. In  coconut water-based extender there was a significant difference in intact plasma membrane percentage at different time slots (0, 24,  48 and 72 h). It was concluded that coconut water-based extender can preserve canine sperm for up to 48 h while maintaining sperm  motility and viability above 50%. Sperm abnormalities remained within 20% and plasma membrane integrity above 60% both were  maintained up to 72 h of semen preservation.
Keywords: Canine semen; Coconut water-based semen extender; Cooled storage